The antidiabetic effects of Bifidobacterium longum subsp. longum BL21 through regulating gut microbiota structure in type 2 diabetic mice. Issue 19 (3rd September 2022) - Hao, Junyu; Zhang, Yongli; Wu, Tao; Liu, Rui; Sui, Wenjie; Zhu, Jianguo; Fang, Shuguang; Geng, Jieting; Zhang, Min
Abstract : Bifidobacterium longum subsp. longum BL21 exerts conspicuous hypoglycemic effects via reshaping the gut microbiota and glucose metabolism, and it could be a potential functional food for controlling type 2 diabetes. Abstract : Bifidobacterium longum subsp. longum BL21 (BL21) possesses hypoglycemic activity, but its anti-diabetic mechanism has rarely been illustrated. In the present work, the effects of BL21 on type 2 diabetes mellitus (T2DM) were investigated in diabetic mice induced via a high-fat diet combined with streptozotocin (STZ). Our data indicated that BL21 at a dose of 10 9 CFU per day significantly lowered the levels of fasting blood glucose and alleviated insulin resistance in diabetic mice. Meanwhile, BL21 enhanced the anti-oxidative capacity, increased the hepatic glycogen content, and significantly decreased the gene expression levels of glucose-6-phosphatase (G6Pase) and phosphoenolpyruvate carboxykinase (PEPCK) in the livers of diabetic mice. Endotoxemia-related inflammation and impaired intestinal barrier function in diabetic mice were also improved using BL21. More importantly, the disturbance of intestinal flora was regulated by BL21, including increased levels of the genera Akkermansia, Alloprevotella, Bacteroides, and Alistipes and decreased levels of Lachnospiraceae_NK4A136_group, Mucispirillum, and Odoribacter . Collectively, the amelioration of T2DM via BL21 supplementation might be partially attributed to regulation of the parameters related to glucose metabolism and the modulation of gut microbiota. Therefore, BL21 could be a potential functional food for ameliorating T2DM.